2007
DOI: 10.1093/annonc/mdm366
|View full text |Cite
|
Sign up to set email alerts
|

A phase I and pharmacokinetic study of lapatinib in combination with infusional 5-fluorouracil, leucovorin and irinotecan

Abstract: The combination of lapatinib and FOLFIRI is safe and demonstrates clinical activity; the documented PK interaction can effectively be compensated by lowering the doses of 5-FU and irinotecan. This regime may be further tested in a phase II trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 4 publications
2
27
0
Order By: Relevance
“…Despite the small numbers this trial compares favourably with historical response rates for 5-FU/irinotecan combinations in second-line treatment of advanced colorectal cancer (disease control rate 34%). The results suggest further study in a phase II trial [11].…”
Section: Clinical Trialsmentioning
confidence: 74%
“…Despite the small numbers this trial compares favourably with historical response rates for 5-FU/irinotecan combinations in second-line treatment of advanced colorectal cancer (disease control rate 34%). The results suggest further study in a phase II trial [11].…”
Section: Clinical Trialsmentioning
confidence: 74%
“…This is evident from phase I clinical data investigating lapatinib and irinotecan (SN-38 is the active metabolite of irinotecan) in combination, which showed that lapatinib significantly altered the pharmacokinetics of SN-38, with an increase in the area under the plasma concentration-time curve of SN-38 for the combination (26). The data presented here therefore have clinical implications, particularly as drug combinations are being given in large randomized studies, whereas unacceptable toxicity has been noted with other combinations (27,28).…”
Section: Discussionmentioning
confidence: 98%
“…Investigators have added lapatinib to chemotherapeutic agents such as paclitaxel (36), docetaxel (37), capecitabine (38), letrozole (39), and to combination regimens such as FOLFOX (40) and FOLFOX (41), with promising results. Although clinical trials in different tumor types are ongoing, the most mature data thus far have been in the treatment of breast cancer, particularly in trastuzumab-resistant patients (37).…”
Section: Discussionmentioning
confidence: 99%